The Relationship between Board of Directors and Risk Management Committee in Malaysia - Ishak, Suhaimi; Mohamad Nor, Mohamad Naimi (Serials Publications, 2017)
The establishment of risk management committee (RMC) in non-banking and non-financial companies is seen as very important.They serve as the crucial elements in risk management process and as the corporate governance mechanism.This study investigates the relationship between the board of directors (BOD) and the establishment of RMC for the non-banking and non-financial companies listed on Bursa Malaysia.Data is collected from the annual reports of companies for the period of 2014 until 2015.Some characteristics of BOD and the establishment of RMC are tested in this study including some control variables.Both descriptive and multivariate analyses are employed to address the research objectives. The results indicate that the BOD size is positively related to the establishment of RMC.Meanwhile, the BOD outside directorship is negatively related to the establishment of RMC.Further, companies audited by big 4 audit firms are positively associated with the establishment of RMC.The findings provide empirical evidence on the development and importance of the BOD and the establishment of RMC for the non-banking and non-financial companies in Malaysia.